Board diversity effects on environmental performance and the moderating effect of board independence: evidence from the Asia-Pacific region - Hamdan Amer Al-Jaifi; Adel Ali Al-Qadasi; Ahmed Hussein Al-Rassas (Cogent Business & Management, 2023)
This study reckons that although a lot of debate has gained currency of late on whether board diversity is associated with environmental performance, empirical evidence that delved into the effects of age, tenure, and gender board diversity and the moderating effect of board independence are yet to be conducted. This study aims to point out how these board diversity attributes can serve as drivers for environmental performance. Using 14,878 firm-year observations from 11 Asia-Pacific countries, the results indicate that the level of environmental performance is positively associated with age and gender board diversity and negatively associated with tenure board diversity. This striking result can be attributed to the management friendliness hypothesis where long-serving on the board is causing a management-friendly bias, which ultimately reduces environmental activities. The findings of this study also support that board independence moderates the associations between tenure and gender diversity and environmental performance. The findings of this study make valuable implications for understanding how board diversity can serve as a driver for the environmental performance issue.
Keywords: 650; age; board diversity; Environmental performance; gender; independence; tenure